Early Child Development as Future Human Resource - Hudtohan, Ma. Perla M.; Hudtohan, Emiliano T.; Arellano, Bernielyn (International Journal of Management and Education in Human Development, 2024)
This narrative presents a longitudinal documentary study on child development; it provides an insight into the basic development of the cognitive, affective and psychomotor skills of a child, who later becomes an adult human resource. It is about parenting and childrearing of an infant from childbirth to one year old. It is focused on the monthly childcare for a period of 12 months, showing the development of a subject named Cyrah. The review of related literature cites the rights of children taken from the documents of the United Nations, the United Nations Children's Fund UNICEF, the 1987 Constitution of the Philippines, and the Family Code of the Philippines. This is a qualitative case study (Marshall & Rossman, 2011; Yin,2006 ) as narrated by Bernilyn Arellano, mother of Cyrah. The approach is storytelling (Pillans, 2014) on early child development in the 21st century. It presents positive parenting tips, infant safety, and healthy infant care practices. Above all, it details the development of Cyrah from birth to year one. Home is the first school for human development and corporate citizenship.